732 Delay to Elective Colorectal Cancer Surgery and its Potential Implications During the Covid-19 Pandemic: A Systematic Review and Metanalysis. (12th October 2021) - Whittaker, T; Abdelrazek, M; Fitzpatrick, A; Froud, J; Kelly, J; Williamson, J; Williams, G
Abstract: Aim: The ongoing Covid-19 pandemic has interrupted the surgical treatment of colorectal cancer (CRC). This systematic review will assess literature concerning the risk of delay of elective surgery for CRC patients, focusing on overall survival (OS) and disease-free survival (DFS). Method: A systematic review was performed as per PRISMA guidelines (PROSPERO ID: CRD42020189158). Medline, EMBASE and Scopus were searched. Delay to elective surgery was defined as the period between CRC diagnosis and the day of surgery. Metanalyses of the outcome's OS and DFS were conducted. Forest plots, funnel plots, and tests of heterogeneity were produced. An estimated Number Needed to Harm (NNH) was calculated for statistically significant pooled Hazard Ratios (HRs). Results: Of 3753 articles identified, seven met the inclusion criteria. Encompassing 314560 patients, three of the seven studies showed that a delay to elective resection is associated with poorer OS or DFS. OS was assessed at a one-month delay, the HR for six datasets was 1.13 (95%CI 1.02-1.26, p = 0.020) and at three months the pooled HR for three datasets was 1.57 (95%CI 1.16-2.12, p = 0.004). Estimated NNHs for a delay at one month and three months were 35 and 10 respectively. Delay was non-significantly negatively associated with DFS on meta-analysis. Conclusions: This review recommends that elective surgery for CRC patients is not postponed, as evidence suggests delays from diagnosis are associated with poorer outcomes. Focused research is essential so that patient groups can be prioritized based on risk factors for future pandemics.